Indonesia di Tengah Rivalitas China, Jepang, dan India: Tinjauan Buku - Alunaza, Hardi (Indonesian Perspective, 2019)
This book consists of 8 chapters that explain the strategic value of the Indo-Pacific region with the presence of strong rivalries such as China, Japan, and India that continue to take place at the regional and global levels which are still colored by the emergence of the role of the US. The first chapter discusses the growth of major powers in world order. The second chapter explains the rivalry of China and Japan in the region. The third chapter describes the rivalry of China and India in the region. The next chapter explains Indonesia and the rivalry of the major powers followed by aggressive Chinese expansion and sluggish Japanese performance. In the last three chapters this book tells a lot about Chinese gunboat diplomacy, the low intensity of Indonesia's relations with India, and conclusion about foreign policy doctrine and Indonesia's response.